Computational Analogies of Polyvinyl Alcohol Fibres Processed Intellgent Systems with Ferrocement Slabs - Prabha , G.; Mohan, A.; Kumar, R. Dinesh; Velrajkumar, G. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Ferrocement composites have distinguished characteristics when compared to other lightweight composites mainly due to its high strength to weight ratio and ductility. Ferrocement panels are being used in low cost housing units with locally available materials. These panels are generally upto 25-50mm thick. Addition of fibres as a secondary reinforcement to ferrocement mortar greatly influenced matrix failure before yielding of the steel mesh. This paper focuses on the experimental study of the flexural behaviour of ferrocement panels with Polyvinyl Alcohol (PVA) fibres.PVA fibres which finds its applications in engineered cementious composites has been selected due to its hydrophilic nature and high tensile strength. High strength cementitious mortar mix consisting of silica fumes and quartz powder at different proportions were developed for casting ferrocement slab panels. Also, polyvinyl alcohol fibres were added at different volume fractions ranging from 1% to 3% to further improve the mechanical properties of the mortar mix. The compressive strength of the optimized mix was 53.47 MPa at 2% PVA fibre. The slabs were casted by placing four layers of 1mm diameter galvanized steel welded mesh with 12mm mesh size. The dimension of the slab was 700mmx300x25mm.The slabs were tested under two point loading in universal testing machine. The comparative study between the ferrocement slab panels with and without PVA fibres on various parameters has been done. These parameters included load vs deformation, stress vs strain , crack patterns, flexural strength and toughness.